Um estudo sobre a contribuição da tecnologia da informação (TI) para a inovação organizacional - Koyama, Cristina (2007)
The study of the innovation creation process dynamic and its importance is recognized and more evidenced by companies of all segments, academical institute and government, as well, in a global context in order to get high levels of competivity and economical development In the same way, Information Technology has great importance, not only due to its role as data provider and decision infrastructure for daily operation of the organization but also because of its actuation in the development and implementation of the organization strategy process, once this makes possible the innovation business, by allowing to change significantly the competitive advantage of the companies In this context, this work aims to perform a study concerning the contribution of the Information Technology for the organizational innovation Moreover, the theoretical development was performed based on the main authors works and subjects related to innovation, strategical administration, theory of the organizations and information technology issues The analysis of the results allowed to identify the adopted information Technology practices, easy and difficulty aspects that IT meet to promote the organizational innovation, and finally investigate possible relation between several studied variable Main difficulty aspects detected were the training lacking, low cooperation between the areas, resistance to changes and the organizations excessively structured On the other hand, main easy aspects described here were high gerency support, leaders, qualified human resources, IT participation in the strategic planning, infrastructure investment and role of the IT director executed efficiently Nevertheless, regarding the tested statistical method of inference, the obtained results show a slight or low association between the variables